Both complete response and long-term survival after combination therapy with toripalimab in a patient with meta-oligometastases cervical cancer: a case report - Jin, Ge; Wang, Jun (Frontiers in Immunology, 2025)
BackgroundThe therapeutic landscape for recurrent or metastatic cervical cancer remains limited, with few options available. According to National Comprehensive Cancer Network (NCCN) guidelines, pembrolizumab combined with chemotherapy, with or without bevacizumab, is recommended for affected patients. Despite these guidelines, recurrence rates remain elevated, and survival outcomes following standard interventions are unsatisfactory. Furthermore, real-world management of recurrent or metastatic cervical cancer presents inherent complexities, often requiring an integrative, multidimensional treatment approach to enhance long-term survival. The pressing need to refine and adopt multimodal therapeutic strategies is evident in addressing the persistent challenges associated with disease recurrence and progression.Case descriptionThe case involved a 40-year-old female diagnosed with advanced cervical cancer who underwent radical hysterectomy. Postoperative pathology identified high-risk features, including lymph node involvement, necessitating adjuvant chemoradiotherapy. However, disease progression occurred during treatment, manifesting as metastases in the left supraclavicular and axillary lymph nodes. Subsequent local radiotherapy and systemic therapy led to a favorable response. By November 2024, overall survival (OS) had surpassed 72 months, with toripalimab administered for 65 months, during which no immunotherapy-related adverse events occurred.ConclusionThis case offers clinical insight into the efficacy and safety of integrating chemotherapy, immunotherapy, and radiotherapy in recurrent or metastatic cervical cancer. The multimodal approach contributes to prolonged survival in this patient. Further clinical trials are essential to substantiate the therapeutic benefits of this regimen in broader patient cohorts.